Produksi Program Acara â€œPro 2 Activityâ€ di Pro 2 RRI Semarang (Pengarah Acara ) - Roli Harni Purba, Juita; Pradekso, Tandiyo (Interaksi Online, 2020)
Radio Republik Indonesia is the oldest radio station in Indonesia and is the only radio owned by the Indonesian government. As a public broadcasting institution, RRI has a vision of realizing an Indonesian public broadcasting institution as a trusted and worldwide radio. RRI has a very wide network, from Aceh to Papua. However, there are still many young people who donâ€™t know Radio Republik Indonesia. The number of private radios that have sprung up today causes the popularity of RRI decreased. In addition, the image of RRI as news radio and radio for parents in the society, so it is considered less attractive for young people who need entertainment and the latest things. In order to make RRI and its programs known to the public, especially young people, one solution that can be done is to re-concept or re-create the program "Pro 2 Activity" with a new concept by involving students and communities as resource persons in this program. During the implementation of this program, the writer is in charge as the program director, who is responsible for making the rundown and managing the program in accordance with the direction of the creative team with the producer. During 8 weeks, the writer and team succeeded in producing 24 episodes of the "Pro 2 Activity" program with a duration of 3 hours in each episode and presenting the youth and communities as resource persons with the concept of the program being packaged differently from before, successfully attract listeners to listen â€œPro 2 Activity Programâ€. Through this program, the writer and team also succeeded in increasing the number of active listeners, which initially only 3 to 4 people in each episode, with a new concept, now the active listeners of "Pro 2 Activityâ€ program is increased 8 to 10 active listeners in each episode.